A high-stability self-absorbing water ice bag and preparation method thereof
By introducing double urea and dynamic thiol compounds into the self-absorbent ice pack, a dynamic network structure is constructed, which solves the problem of insufficient stability in the freeze-thaw cycle of existing ice packs, and the effects of enhanced ice pack strength, water absorption maintenance and improved antibacterial performance are achieved.
Patent Information
- Application Number
- CN202510247431.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing self-absorbent water ice packs have insufficient stability during the freezing and thawing cycle, resulting in a decrease in water absorption capacity, weakening of strength, significantly reducing the refrigeration effect, and shortening the service life.
By introducing biurea and dynamic thiol compounds, they work together with flexible crosslinking agents, nanoreinforced materials and multiple antibacterial agents to build a three-dimensional interpenetrating dynamic network structure to achieve dynamic self-healing and gradual enhancement of gel strength in the cryothing cycle.
The gradual enhancement of the strength of the ice pack after multiple freeze-thaw cycles is achieved, maintaining high water absorption and flexibility, significantly extending the service life, and improving antibacterial performance and freeze-thaw stability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to an ice bag and a preparation method thereof, in particular to a high-stability self-absorbent water ice bag and a preparation method thereof. Background Art
[0002] Self-absorbent water ice packs are an important refrigeration product. This product is mainly made of polymer water-absorbing materials, which can absorb a large amount of water and form ice gel after freezing, thereby achieving a continuous cooling effect. The existing self-absorbent water ice pack preparation process is usually: first, the polymer monomer is mixed with the cross-linking agent to form a three-dimensional network structure through free radical polymerization; then the obtained dry gel is ground into particles and packed into a plastic bag; finally, a certain amount of water is added to make it absorb water and swell, forming a hydrogel with a certain strength. This hydrogel can maintain a low temperature for a considerable period of time after freezing and has the characteristics of being reusable.
[0003] However, in actual applications, the existing self-absorbent ice packs have serious performance degradation problems. The primary problem is the lack of stability of the cross-linked structure. During repeated freezing and thawing, the chemical bonds in the gel network are easily broken, which directly leads to a decrease in the gel's water absorption capacity, while also weakening the gel's strength, causing softening and rheological phenomena. Especially after multiple uses, the product's cooling effect will be significantly reduced and its service life will be greatly shortened.
[0004] The freeze-thaw cycle will damage the internal structure of the gel. When water molecules freeze, they expand in volume. This repeated expansion and contraction will destroy the microstructure of the gel, causing the gel particles to agglomerate and even to show obvious stratification, reducing its refrigeration performance and comfort.
[0005] Therefore, it is of great significance to develop a new type of self-absorbent water ice bag. Summary of the invention
[0006] The purpose of the present invention is to provide a high-stability self-absorbent water ice bag and a preparation method thereof. The high-stability self-absorbent water ice bag and the preparation method thereof construct a three-dimensional interpenetrating dynamic network structure by introducing biuret and dynamic thiol compounds, synergistically acting with flexible crosslinking agents, nano-reinforced materials and multiple antimicrobial agents, and achieve dynamic self-repair and gradual enhancement of gel strength in the freeze-thaw cycle.
[0007] The above technical objectives of the present invention are achieved through the following technical solutions: A high-stability self-absorbent ice bag comprises the following components in parts by mass: 65-75 parts of acrylic acid; 10-12 parts of sodium acrylate; 3-5 parts of a flexible crosslinking agent; 5-8 parts of a chitosan grafting monomer; 2-3 parts of biuret; 1-2 parts of a dynamic thiol compound; 0.5-2 parts of nano-silicon dioxide; 0.3-0.5 parts of a nano-silver / zinc oxide composite; 1-2 parts of modified montmorillonite; 2-3 parts of an antibacterial agent microcapsule; and 0.1-0.3 parts of an initiator. The ice bag has a reversible thiol-disulfide crosslinking network formed by the dynamic thiol compound and hydrogen bonds of the biuret, so that the ice bag can dynamically self-repair during freezing and thawing cycles and has cyclically enhanced gel strength.
[0008] By adopting the above technical scheme: by introducing dynamic thiol compounds and biuret, a dynamic reversible three-dimensional network structure is constructed: the dynamic cross-linking of thiol-disulfide bonds enhances the anti-freeze-thaw ability of the gel and can self-repair microcracks caused by freezing stress. The hydrogen bonding of biuret further stabilizes the network, enhances the rigidity in the frozen state, and dynamically rebuilds the intermolecular interactions around the cracks after thawing. The flexible cross-linker provides a flexible chemical cross-linking network to buffer the internal stress during the freeze-thaw cycle. Nano-reinforcement materials (nano-silicon dioxide and modified montmorillonite) improve the mechanical strength and crack resistance of the gel and prevent particle agglomeration and stratification. Multiple antimicrobial agents (nano-silver / zinc oxide complex and antimicrobial agent microcapsules) combined with microcapsule sustained-release technology achieve long-lasting antibacterial effects and avoid odor and performance degradation. The unique effect of gradually enhancing gel strength during the freeze-thaw cycle is achieved while maintaining high water absorption.
[0009] The present invention is further configured as follows: the flexible cross-linking agent is polyethylene glycol diacrylate, and the initiator is ammonium persulfate.
[0010] By adopting the above technical solution: the introduction of flexible cross-linking agent (polyethylene glycol diacrylate) provides low rigidity and high flexibility cross-linking points, which can buffer the stress concentration in the freeze-thaw cycle, significantly improve the crack resistance and prevent stratification. The existence of the flexible network enables the ice pack to maintain excellent water absorption and flexibility after multiple freeze-thaw cycles. The initiator (ammonium persulfate) as a highly efficient free radical initiator ensures the uniformity and high conversion rate of the polymerization reaction, ensures the full progress of the chitosan grafting reaction and the main polymerization reaction, and forms a stable gel structure.
[0011] The present invention is further configured as follows: the dynamic thiol compound forms a disulfide bond in a frozen state to enhance network rigidity through a reversible thiol-disulfide cross-linking reaction, and breaks into thiol groups in a thawed state, thereby releasing cross-linking point stress and repairing microcracks; the biuret molecule participates in the regulation of network stability through hydrogen bonding, forms a stable hydrogen bond network in a frozen state, and repairs microcracks caused by freezing stress through dynamic reconstruction in a thawed state.
[0012] By adopting the above technical solution: the reversible cross-linking reaction of thiol-disulfide bonds of dynamic thiol compounds: disulfide bonds are formed during freezing, which increases the rigidity of the gel and resists the mechanical stress of ice crystal formation; when thawed, it breaks into thiol groups, releases the stress of the cross-linking points, and repairs microcracks at the same time to avoid cumulative damage from freeze-thaw cycles. The hydrogen bonds of biuret form a stable intermolecular hydrogen bond network in the frozen state to support and stabilize the gel structure; when thawed, the dynamic reconstruction of hydrogen bonds optimizes the intermolecular interaction around the cracks, further improving the strength and toughness of the gel. During the freeze-thaw cycle, the dynamic cross-linking and hydrogen bonding work together to make the ice pack show a unique effect of self-repairing ability and gradually enhanced strength.
[0013] A method for preparing the above self-absorbent water ice bag comprises the following steps: (1) preparing chitosan grafting monomer; (2) preparing nano silver / zinc oxide composite antibacterial agent; (3) preparing antibacterial agent microcapsules; (4) carrying out a main polymerization reaction: adding acrylic acid, sodium acrylate, a flexible crosslinking agent, chitosan grafting monomer, biuret, a dynamic thiol compound, nano silicon dioxide, a modified nano silver / zinc oxide composite, a modified montmorillonite and antibacterial agent microcapsules to deionized water in sequence, adjusting the pH to 7.0-8.0; reacting at 60-70° C. for 3 hours under nitrogen protection; drying and crushing the product to 100-200 μm; and (5) encapsulating.
[0014] By adopting the above technical scheme: through a multi-step preparation process (including the preparation of chitosan grafted monomers, composite antibacterial agents and microcapsules), the functional modification of each component is ensured, and the following are achieved: chitosan grafted monomers provide antibacterial activity; nanosilver / zinc oxide composite antibacterial agents enhance the antibacterial effect and form a synergistic antibacterial system with chitosan; antibacterial agent microcapsules extend the duration of antibacterial performance by slowly releasing antibacterial substances. The main polymerization reaction regulates the crosslinking density and dispersibility of the gel, ensuring the water absorption, strength and dynamic self-healing ability of the gel.
[0015] The present invention is further configured as follows: the step of preparing the chitosan grafted monomer comprises: dissolving chitosan with a deacetylation degree of ≥90% and a relative molecular weight of 100,000-200,000 in a 1% acetic acid solution, stirring until completely dissolved to form a uniform and transparent chitosan solution; performing a grafting reaction according to a chitosan to acrylic acid mass ratio of 1:4, that is, slowly dripping into the chitosan solution at a ratio of 1:4, maintaining a stirring speed of 300 rpm; adding 0.1% initiator, reacting in a 60°C water bath for 2 hours to form a grafted modified chitosan solution; using anhydrous ethanol precipitation, washing, and drying at 60°C for 12 hours to obtain chitosan grafted monomer powder.
[0016] By adopting the above technical solution: the chitosan grafted monomer significantly improves the dispersibility and reactivity of chitosan through the grafting reaction of acrylic acid: the newly added carboxyl and amino groups formed by grafting participate in hydrogen bonding, enhancing the stability of the gel network; the cationic properties of chitosan destroy the bacterial cell wall and provide long-lasting antibacterial properties. The process removes unreacted monomers and impurities through ethanol precipitation and drying, ensuring the purity and performance of the product.
[0017] The present invention is further configured as follows: the step of preparing the nano silver / zinc oxide composite antibacterial agent comprises: dispersing 50 nm zinc oxide in deionized water with a mass concentration of 5%, ultrasonically dispersing for 30 minutes, adding 0.1% Tween-80, and continuing to stir for 1 hour to improve the dispersibility of zinc oxide; slowly dripping 0.1 mol / L silver nitrate solution in the above zinc oxide dispersion to control the silver ion concentration to 2 wt%. Under stirring conditions, adding a reducing agent of 0.2 mol / L glucose solution, maintaining the reaction temperature at 80°C, reacting for 1 hour, generating surface-loaded nano silver zinc oxide composite particles; adding 1% quaternary ammonium salt solution to the nano silver / zinc oxide composite particles, stirring at 60°C for 2 hours for surface modification, then washing with deionized water 3 times, and drying to obtain a modified nano silver / zinc oxide composite.
[0018] By adopting the above technical scheme: surface modification of zinc oxide and in-situ loading of nanosilver: nanosilver releases silver ions (Ag + ) combines with the sulfhydryl group (-SH) of bacteria to inhibit cell respiration and DNA replication; zinc oxide releases zinc ions (Zn 2+ ) and reactive oxygen species (superoxide anions, hydroxyl radicals), inducing oxidative stress on bacterial membranes. Surface modification with quaternary ammonium salts enhanced the dispersibility and antibacterial activity of the composite particles, while improving their compatibility with the gel matrix.
[0019] The present invention is further configured as follows: the step of preparing the antibacterial agent microcapsule comprises: taking the antibacterial essential oil as the core material, adding a solvent to dilute it, stirring at a high speed of 1000 rpm, adding dropwise into deionized water to form an emulsion, dissolving gelatin in deionized water at 50° C. to form a 10% gelatin solution, slowly adding the solution into the emulsion, maintaining a stirring speed of 500 rpm, then adding a 0.5% glutaraldehyde solution at a mass ratio of 1:10 to gelatin, reacting at 50° C. for 2 hours to form a stable microcapsule structure, after the reaction is completed, cooling the microcapsule emulsion to room temperature, precipitating the microcapsules with anhydrous ethanol, repeating the washing for 3 times, and finally drying in a vacuum drying oven at 40° C. for 12 hours to obtain the antibacterial agent microcapsule powder.
[0020] By adopting the above technical solution: the microcapsules use gelatin as the wall material and form a stable structure through glutaraldehyde cross-linking: gradually release antibacterial essential oils (such as tea tree essential oil) in a humid environment, significantly extending the duration of antibacterial properties; effectively avoid direct precipitation of antibacterial substances, prevent odor and gel performance degradation.
[0021] The present invention is further configured as follows: the main polymerization reaction step is specifically as follows: adding acrylic acid and sodium acrylate into deionized water, stirring until completely dissolved, adjusting the pH to 7.0-8.0, and sequentially adding a flexible crosslinking agent, a chitosan grafting monomer, biuret, a dynamic thiol compound, nano-silicon dioxide, a modified nano-silver / zinc oxide composite, a modified montmorillonite and an antibacterial agent microcapsule under stirring conditions, stirring until each component is evenly dispersed, and then adding 0.1% initiator; under nitrogen protection, heating the mixed solution to 60-70° C., maintaining a stirring speed of 300 rpm, and a reaction time of 3 hours. After the polymerization is completed, cooling to room temperature to obtain a gel product; placing the gel in an oven at 80° C. and drying to constant weight, and then using a grinder to grind the dried gel into particles with a particle size of 100-200 μm to obtain a target powder product.
[0022] By adopting the above technical scheme: during the main polymerization process, acrylic acid and sodium acrylate provide the water absorption basis of the gel; dynamic thiol compounds and biuret are evenly dispersed during the polymerization process, forming a dynamic reversible thiol-disulfide bond and hydrogen bond network: ensuring the dynamic repair ability in the freeze-thaw cycle; improving the gel strength and crack resistance. Nano-silica, modified montmorillonite and other nano-reinforcement materials further improve the mechanical strength of the gel.
[0023] The present invention is further configured as follows: the packaging step includes: using a three-layer co-extruded film, wherein the outer layer is high-density polyethylene with a thickness of 70 μm, the middle layer is ethylene-vinyl acetate copolymer with a thickness of 40 μm, and the inner layer is linear low-density polyethylene with a thickness of 50 μm, putting the prepared gel powder into a three-layer composite film bag, and sealing it with a heat sealer.
[0024] By adopting the above technical solution: using three-layer co-extrusion film: outer layer HDPE: provides high strength and puncture resistance; middle layer EVA: provides good flexibility to adapt to freezing expansion; inner layer LLDPE: provides excellent sealing and waterproof performance. The heat sealing process ensures the firmness and sealing of the package, avoiding the leakage of the ice bag during use.
[0025] The present invention is further configured as follows: the heat sealing process parameters of the three-layer composite film are: temperature 135±5° C.; pressure 0.6±0.1 MPa; time 1.5±0.2 s.
[0026] By adopting the above technical solution: accurately controlling the heat sealing temperature, pressure and time: ensuring the firm heat sealing of the three-layer composite film, avoiding leakage caused by poor heat sealing; improving the durability and reliability of the ice pack, meeting the demand for maintaining good performance after multiple freezing and thawing.
[0027] In summary, the present invention has the following beneficial effects: The present invention utilizes the synergistic effect of biuret and dynamic thiol compounds to construct a three-dimensional dynamic cross-linked network, and simultaneously combines multiple antibacterial components to achieve long-lasting antibacterial performance.
[0028] 1. Synergistic mechanism of biuret and dynamic thiol compounds in frozen and thawed states (1) Hydrogen bonding of biuret The biuret (H2N-CO-NH-CO-NH2) molecular structure contains multiple carbonyl groups (C=O) and amino groups (-NH2), which can participate in the stability regulation of the gel network through intermolecular hydrogen bonds: The carbonyl group (C=O) acts as a hydrogen bond acceptor and forms hydrogen bonds with other molecular hydrogen bond donors (such as thiol group -SH, chitosan grafted monomers, etc.). The amino group (-NH2) acts as a hydrogen bond donor and forms hydrogen bonds with carbonyl groups, dynamic thiol compounds and other groups in the network. During the freezing and thawing process, the hydrogen bonding of biuret is a dynamic reversible process: Frozen state: At low temperatures, hydrogen bonds tend to be stable, and the biuret molecules form more hydrogen bonds through their carbonyl and amino groups, building a gel network that obtains higher rigidity to resist the mechanical stress caused by ice crystal formation.
[0029] Thawed state: As the temperature rises and water molecules redistribute, some hydrogen bonds break, but dynamic hydrogen bonds can be quickly rebuilt to repair microcracks caused by freezing stress while maintaining the flexibility and water absorption capacity of the network.
[0030] (2) Reversible thiol-disulfide bond interaction of dynamic thiol compounds The thiol group (-SH) in the dynamic thiol compound undergoes a reversible thiol-disulfide crosslinking reaction through a redox reaction, which regulates the dynamic crosslinking point during the freezing and thawing process: Frozen state: During the freezing process, dissolved oxygen (O2) in the system oxidizes thiol groups to generate disulfide bonds (-SS-), forming cross-linking points, which enhance the rigidity of the network to resist the tensile stress caused by ice crystal formation. The reaction formula is: 2R-SH+1 / 2O2→RSS-R+H2O Thawed state (reduction reaction): During the thawing process, disulfide bonds break into thiol groups under the action of low oxygen environment or reducing molecules, releasing the stress of the cross-linking points, dynamically adjusting the network structure, and repairing the microcracks caused by freezing. The reaction formula is: RSS-R+2[H]→2R-SH.
[0031] (3) Synergistic effect of biuret and dynamic thiol compounds Combination of dynamic cross-linking and hydrogen bonding: When frozen, the dynamic thiol compounds form disulfide bonds to provide the necessary rigid support; the hydrogen bonding between the biuret and the dynamic thiol compounds or other components further stabilizes the network structure and prevents breakage caused by ice crystal stress.
[0032] When thawed, the disulfide bonds break to release the stress at the cross-linking points, and the hydrogen bonds between the biuret and the dynamic thiol compounds are dynamically rebuilt, effectively repairing microcracks and restoring flexibility.
[0033] Dynamic thiol compounds provide network dynamic regulation capabilities through chemical cross-linking (thiol-disulfide bonds); Biuret provides non-covalent stability between molecules through physical hydrogen bonds, and the two combine to construct a three-dimensional network with dynamic adaptability.
[0034] 2. The technical effect of gradual enhancement of gel strength during multiple freezing cycles (1) Accumulation of thiol-disulfide crosslinks The thiol-disulfide bonds of the dynamic thiol compounds generate new cross-linking points when frozen, but they are not completely reduced when thawed, and some disulfide bonds remain. This gradual accumulation of cross-linking points leads to a continuous increase in the cross-linking density of the gel, thereby significantly improving the strength of the gel.
[0035] (2) Dynamic rearrangement and optimization of hydrogen bonds The hydrogen bonds of biuret undergo a process of breaking and rebuilding during the freeze-thaw cycle, and the hydrogen bond distribution at the cracks is optimized, making the network structure more uniform and enhancing the toughness and stability of the gel.
[0036] (3) Rearrangement and densification of network structure During the freeze-thaw cycle, the mechanical stress exerted by ice crystals on the network causes local rearrangement of the molecular chains, and the self-repairing effect of dynamic cross-linking points and hydrogen bonds fills the original loose areas during thawing. After each cycle, the network structure becomes denser and more uniform, thereby improving the tensile and compressive strength of the gel.
[0037] (4) Improvement of crack resistance After multiple freeze-thaw cycles, the reversible cross-linking of the dynamic thiol compounds and the hydrogen bonding of the biuret repaired the microcracks and optimized the cross-linking structure around the cracks, gradually enhancing the gel's resistance to crack propagation and showing higher crack resistance.
[0038] 3. As the gel strength increases, the properties of the gel will continue to change, as follows: (1) Improvement of mechanical properties Tensile strength: The increase in cross-linking density and intermolecular forces after freeze-thaw cycles makes the gel exhibit higher tensile strength.
[0039] Compression strength: Network densification and accumulation of cross-linking points improve the compressive properties of the gel.
[0040] Elastic modulus: The optimization of dynamic cross-linking points and the reconstruction of hydrogen bonds increase the elastic recovery ability of the gel.
[0041] (2) Balance between water absorption and flexibility The cross-linking density increases, but the reversibility of the dynamic cross-linking points and the hydrogen bonding of the biuret ensure that the water absorption and flexibility of the gel will not be significantly reduced, meeting the needs of practical applications.
[0042] (3) Freeze-thaw stability Tests showed that the water absorption retention rate was ≥90% after 100 freezing cycles, indicating that the dynamic cross-linking network maintained a high stability during multiple freeze-thaw processes.
[0043] In summary, the present invention constructs a three-dimensional gel network with dynamic regulation function through the reversible thiol-disulfide cross-linking reaction of dynamic thiol compounds and the hydrogen bonding of biuret. In the frozen state, thiol is oxidized to generate disulfide bonds to increase cross-linking points; in the thawed state, disulfide bonds break to repair cracks, and hydrogen bonds dynamically rebuild and optimize the network structure. In multiple freeze-thaw cycles, the accumulation of cross-linking density, rearrangement of hydrogen bonds and network densification gradually enhance the strength of the gel while maintaining excellent water absorption and flexibility.
[0044] The method for preparing a high-stability self-absorbent ice bag of the present invention realizes dynamic self-repairing ability, high mechanical strength, long-lasting antibacterial performance and freeze-thaw cycle stability that cannot be achieved by traditional ice bags.
[0045] The introduction of dynamic thiol compounds and biuret constructs a dynamic reversible three-dimensional cross-linked network. The dynamic thiol compounds form disulfide bonds in the frozen state through the reversible cross-linking reaction of thiol-disulfide bonds to enhance the network rigidity to resist ice crystal stress, while in the thawed state, the disulfide bonds break to release the stress at the cross-linking points and repair the microcracks caused by freeze-thaw. At the same time, the biuret molecules form a stable hydrogen bond network through their carbonyl and amino groups, which enhances the mechanical strength of the gel in the frozen state, and dynamically rebuilds the intermolecular interactions at the cracks during the thawing process, so that the network is gradually optimized and the dynamic self-repairing ability of the ice pack is realized, so that the performance does not decrease after multiple freeze-thaw cycles, but the gel strength is gradually enhanced, solving the problem of performance degradation of traditional ice packs due to the breakage of cross-linking points.
[0046] After chitosan was modified by acrylic acid grafting, its reactivity and dispersibility were significantly increased. The newly added carboxyl and amino groups formed by grafting not only participate in hydrogen bonding and enhance the network stability of the gel, but also destroy the bacterial cell wall through the cationic properties of chitosan, and synergize with the multiple antibacterial mechanisms of nanosilver and zinc oxide to effectively inhibit bacterial reproduction. Nanosilver inhibits bacterial DNA replication by releasing silver ions, zinc oxide induces oxidative stress of cell membranes by releasing reactive oxygen, and quaternary ammonium salts further enhance the antibacterial effect by destroying the bacterial membrane structure. In addition, the antibacterial agent microcapsule sustained-release technology ensures the gradual release of antibacterial ingredients in a humid environment, significantly prolongs the duration of the antibacterial effect, and avoids the odor and performance degradation caused by the precipitation of antibacterial agents in traditional ice packs.
[0047] Nano-silica and modified montmorillonite significantly improve the mechanical strength and crack resistance of the gel network through physical reinforcement, while preventing particle agglomeration and stratification. During the main polymerization process, the introduction of a flexible cross-linking agent (polyethylene glycol diacrylate) provides a flexible chemical cross-linking network, which effectively buffers the internal stress during freeze-thaw cycles and further enhances the stability and flexibility of the gel. The uniform distribution of the dynamic network and the fine control of the cross-linking density ensure that the water absorption retention rate of the ice pack is ≥90% after 100 freeze-thaw cycles, while achieving excellent performance of a water absorption rate of up to 450g / g.
[0048] In terms of packaging, the three-layer composite film (HDPE / EVA / LLDPE) design, combined with an optimized heat-sealing process, ensures the durability and sealing of the ice pack. High-density polyethylene (HDPE) provides puncture resistance, ethylene-vinyl acetate copolymer (EVA) provides flexibility to adapt to freezing expansion, and linear low-density polyethylene (LLDPE) enhances water tightness, so that the ice pack does not leak during multiple freezing and thawing processes.
[0049] The self-absorbent ice bag preparation method of the present invention achieves performance improvement of the ice bag through dynamic network regulation, multiple antibacterial mechanisms, synergistic effect of nano-reinforced materials and refined process control, significantly improves the mechanical strength, antibacterial duration and freeze-thaw cycle stability of the ice bag, and overcomes the problem of performance degradation of traditional ice bags caused by cross-linking point breakage, particle agglomeration and antibacterial agent precipitation. DETAILED DESCRIPTION
[0050] A high-stability self-absorbing water ice bag comprises the following components by mass distribution ratio: 65-75 parts of acrylic acid; 10-12 parts of sodium acrylate; 3-5 parts of polyethylene glycol diacrylate; 5-8 parts of chitosan grafted monomer; 2-3 parts of biuret; 1-2 parts of dynamic thiol compound; 0.5-2 parts of nano silicon dioxide; 0.3-0.5 parts of nano silver / zinc oxide complex; 1-2 parts of modified montmorillonite; 2-3 parts of antibacterial agent microcapsules; and 0.1-0.3 parts of ammonium persulfate.
[0051] A method for preparing a high-stability self-absorbing water ice bag comprises the following steps: (1) Preparation of chitosan grafted monomer: dissolving chitosan with a deacetylation degree of ≥90% and a relative molecular weight of 100,000-200,000 in 1% acetic acid solution, stirring until completely dissolved to form a uniform and transparent chitosan solution; performing a grafting reaction at a chitosan to acrylic acid mass ratio of 1:4, i.e. slowly adding the chitosan to acrylic acid in a ratio of 1:4, maintaining a stirring speed of 300 rpm; adding 0.1% initiator, reacting in a 60°C water bath for 2 hours to form a grafted modified chitosan solution; precipitating with anhydrous ethanol, washing, and drying at 60°C for 12 hours to obtain chitosan grafted monomer powder.
[0052] (2) Preparation of nanosilver / zinc oxide composite antibacterial agent: 50 nm zinc oxide was dispersed in deionized water with a mass concentration of 5%. After ultrasonic dispersion for 30 minutes, 0.1% Tween-80 was added and stirring was continued for 1 hour to improve the dispersibility of zinc oxide. 0.1 mol / L silver nitrate solution was slowly added to the above zinc oxide dispersion to control the silver ion concentration to 2 wt%. Under stirring conditions, 0.2 mol / L glucose solution was added as a reducing agent, the reaction temperature was maintained at 80°C, and the reaction was carried out for 1 hour to generate surface-loaded nanosilver zinc oxide composite particles. 1% quaternary ammonium salt solution was added to the nanosilver / zinc oxide composite particles, stirred at 60°C for 2 hours for surface modification, and then washed with deionized water 3 times and dried to obtain modified nanosilver / zinc oxide composite.
[0053] (3) Preparation of antibacterial agent microcapsules: Antibacterial essential oil was taken as the core material, diluted with solvent, stirred at a high speed of 1000 rpm, and added dropwise into deionized water to form an emulsion. Gelatin was dissolved in deionized water at 50°C to form a 10% gelatin solution, which was slowly added into the emulsion while maintaining a stirring speed of 500 rpm. Subsequently, a 0.5% glutaraldehyde solution was added at a mass ratio of 1:10 to gelatin, and the mixture was reacted at 50°C for 2 hours to form a stable microcapsule structure. After the reaction was completed, the microcapsule emulsion was cooled to room temperature, and the microcapsules were precipitated with anhydrous ethanol. The washing was repeated 3 times, and finally, the antibacterial agent microcapsule powder was obtained by drying at 40°C in a vacuum drying oven for 12 hours.
[0054] (4) Conducting a main polymerization reaction: adding acrylic acid and sodium acrylate to deionized water, stirring until completely dissolved, adjusting the pH to 7.0-8.0, and adding a flexible crosslinker, chitosan grafting monomer, biuret, dynamic thiol compound, nano-silica, modified nano-silver / zinc oxide composite, modified montmorillonite and antibacterial agent microcapsules in sequence under stirring, stirring until all components are evenly dispersed, and then adding 0.1% initiator; under nitrogen protection, heating the mixed solution to 60-70°C, maintaining the stirring speed at 300 rpm, and the reaction time is 3 hours. After the polymerization is completed, cooling to room temperature to obtain a gel product; placing the gel in an oven at 80°C to dry to constant weight, and then using a grinder to grind the dried gel into particles with a particle size of 100-200 μm to obtain a target powder product; (5) Packaging: A three-layer co-extruded film is used, wherein the outer layer is high-density polyethylene with a thickness of 70 μm, the middle layer is ethylene-vinyl acetate copolymer with a thickness of 40 μm, and the inner layer is linear low-density polyethylene with a thickness of 50 μm. The prepared gel powder is loaded into a three-layer composite film bag and sealed with a heat sealer. The heat sealing process parameters are: temperature 135±5°C; pressure 0.6±0.1MPa; time 1.5±0.2s.
[0055] According to the above self-absorbent water ice bag and its preparation method, the following experiment was designed: According to the experimental grouping, as shown in Table 1: Table 1: Data table of experimental group and control group
[0056] According to the above experimental design, the following experiments were conducted on the above experimental groups, mainly testing their mechanical property improvement, water absorption and flexibility balance, and freeze-thaw stability.
[0057] Experiment 1: Mechanical properties test Experimental purpose: To test the tensile strength, compressive strength and elastic modulus of the ice pack after freeze-thaw cycles, and to verify the effect of optimizing the dynamic cross-linking points and hydrogen bond network on improving the mechanical properties.
[0058] Experimental steps: 1. Prepare samples of different experimental groups (experimental groups 1-4, control groups 1-2).
[0059] 2. In the frozen (-20℃) and thawed (25℃) states, use a tensile testing machine and a compression testing machine to test the tensile strength, compressive strength and elastic modulus of the samples respectively.
[0060] 3. Repeat the freeze-thaw cycle test 50 times and measure again to analyze the performance changes.
[0061] Test standard: Tensile strength: refer to GB / T1040.2-2022; Compressive strength: refer to GB / T1041-2008; Elastic modulus: calculated using tensile stress-strain curve.
[0062] Testing equipment: Tensile testing machine (accuracy 0.01MPa); Compression testing machine (accuracy 0.01MPa).
[0063] Experiment 2: Water absorption and flexibility balance test Experimental purpose: To verify whether the increase in cross-linking density has a significant impact on water absorption and flexibility, and to ensure that the water absorption and flexibility of the gel meet the needs of practical applications.
[0064] Experimental steps: 1. Measure the water absorption rate of each group of samples in the initial state.
[0065] 2. Test the water absorption of the sample after 50 freeze-thaw cycles and record the change in flexibility (bending angle change).
[0066] 3. Use a dynamic mechanical analyzer (DMA) to test the storage modulus and loss modulus of the sample and analyze the balance between flexibility and water absorption performance.
[0067] Test standard: Water absorption: refer to GB / T35793-2017, the calculation formula is: Water absorption rate = (mass after water absorption - dry mass) / dry mass; Flexibility: Use a bending tester to record the bending angle of the sample (unit: °).
[0068] Testing equipment: Dynamic Mechanical Analyzer (DMA). Bending tester (accuracy 1°) Experiment 3: Freeze-thaw stability test Experimental purpose: To verify the ability of dynamic cross-linking points to maintain during multiple freeze-thaw cycles and to test the retention rate of water absorption after 100 freeze-thaw cycles.
[0069] Experimental steps: 1. Place the sample in a freezer (-20°C) for 24 hours, and then thaw it at room temperature (25°C) for 24 hours as a freeze-thaw cycle; 2. After every 10 freeze-thaw cycles, record the water absorption of the sample until 100 freeze-thaw cycles are completed.
[0070] 3. Calculate water absorption retention rate: Water absorption retention rate (%) = (water absorption after multiple freeze-thaw cycles / initial water absorption rate) × 100% Test standard: Freeze-thaw stability: After 100 freeze-thaw cycles, the water absorption retention rate is ≥90% to pass.
[0071] Test equipment: Freezer (-20℃±1℃); electronic balance (accuracy 0.01g).
[0072] Experiment 4: Testing the gradual improvement of gel strength under multiple freeze-thaw cycles Purpose: By measuring the changes in the mechanical properties (tensile strength, compressive strength, elastic modulus) and cross-linking density of the samples after multiple freeze-thaw cycles, the gradual increase in gel strength during freeze-thaw cycles was verified.
[0073] Experimental procedures Sample preparation: Each group of samples (experimental group 1 to experimental group 4) was prepared and dried to constant weight, and the mechanical properties and crosslinking density in the initial state were recorded.
[0074] Freeze-thaw cycle: Place the sample in a freezer (-20°C) for 24 hours, and then thaw it at room temperature (25°C) for 24 hours to complete a freeze-thaw cycle. Test the tensile strength, compressive strength, elastic modulus and cross-linking density of the sample every 10 freeze-thaw cycles until 50 freeze-thaw cycles are completed.
[0075] Determination of crosslink density: Measure the swelling ratio (Q) of the sample and calculate the crosslink density using the Flory-Rehner formula: Crosslink density (ν) = -[ln(1-Q)+Q+χQ²] / (V0(Q-1 / 3-Q / 2)); where χ is the solvent-polymer interaction parameter and V0 is the solvent molar volume.
[0076] Test standards: Tensile strength: refer to GB / T1040.2-2022; Compressive strength: refer to GB / T1041-2008; Elastic modulus: calculated using tensile stress-strain curve. Crosslink density calculation: using swelling experiment combined with Flory-Rehner model.
[0077] Test equipment: Tensile testing machine (accuracy 0.01MPa). Compression testing machine (accuracy 0.01MPa). Swelling test equipment (accuracy 0.01g). According to the above experimental design, the following experimental results are obtained: Table 2: Experiment 1: Mechanical properties test
[0078] Table 3: Experiment 2: Water absorption and flexibility balance test
[0079] Table 4: Experiment 3: Freeze-thaw stability test
[0080] Table 5: Experiment 4: Changes in mechanical properties with freeze-thaw cycles
[0081] Table 6: Changes in crosslink density with freeze-thaw cycles
[0082] Based on the above experimental results, the following conclusions are obtained: Improved mechanical properties: Experimental group 1 showed the highest tensile strength (0.85MPa), compressive strength (2.10MPa) and elastic modulus (0.72MPa) in the frozen and thawed state, verifying the significant improvement of mechanical properties by the synergistic effect of dynamic thiol compounds and biuret. The mechanical properties of control group 2 (without nano-reinforcement materials) dropped significantly, with a tensile strength of only 0.60MPa, verifying the importance of nano-reinforcement materials.
[0083] Balance between water absorption and flexibility: The water absorption retention rate of experimental group 1 after 100 freeze-thaw cycles was 91.1%, and the bending angle was 105°, which verified that the reversibility of the dynamic cross-linking points and the hydrogen bonding effect of biuret can maintain the balance between water absorption and flexibility.
[0084] Freeze-thaw stability: The water absorption retention rate of experimental group 1 after 100 freeze-thaw cycles reached 91.1%, which met the standard of ≥90%, verifying the stability of the dynamic network during multiple freeze-thaw cycles. The water absorption retention rate of experimental group 4 (without dynamic network) was only 77.8%, indicating that the dynamic network is the key to freeze-thaw stability.
[0085] The gel strength gradually increased: Experimental group 1 showed a significant strength improvement, with the tensile strength gradually increasing from 0.85MPa to 0.95MPa, and the cross-linking density increasing from 0.025mol / m³ to 0.033mol / m³, verifying the cumulative effect of the dynamic network.
[0086] Dynamic network effect: The limited increase in strength and crosslink density of Experimental Groups 2 and 3 indicates that a single dynamic thiol compound or biuret is not sufficient to achieve significant performance improvement.
[0087] Analysis of control groups: The performance of control group 1 (without antibacterial component) is close to that of experimental group 1, indicating that the antibacterial component has no significant effect on the dynamic network and mechanical properties. The strength and crosslinking density of control group 2 (without reinforcing component) have limited growth, verifying the importance of nano-reinforcement components in improving performance.
[0088] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A high-stability self-absorbing water ice bag, characterized in that: The composition is made by mass ratio, including the following components: Acrylic acid 65-75 parts; Sodium acrylate 10-12 parts; 3-5 parts of flexible cross-linking agent; 5-8 parts of chitosan grafting monomer; Biuret 2-3 parts; 1-2 parts of dynamic thiol compound; Nano silicon dioxide 0.5-2 parts; 0.3-0.5 parts of nano silver / zinc oxide complex; 1-2 parts of modified montmorillonite; 2-3 parts of antibacterial microcapsules; Initiator 0.1-0.3 parts; The ice pack has a reversible thiol-disulfide cross-linking network formed by dynamic thiol compounds and hydrogen bonds of biuret, which enables the ice pack to dynamically self-repair during freezing and thawing cycles and enhance gel strength cycles.
2. The self-absorbent ice bag according to claim 1, characterized in that: The flexible cross-linking agent is polyethylene glycol diacrylate, and the initiator is ammonium persulfate.
3. The self-absorbent ice bag according to claim 2, characterized in that: The dynamic thiol compound forms disulfide bonds to enhance network rigidity in a frozen state through a reversible thiol-disulfide cross-linking reaction, and breaks into thiol groups in a thawed state, thereby releasing cross-linking point stress and repairing microcracks. The biuret molecule participates in the regulation of network stability through hydrogen bonding, forms a stable hydrogen bond network in a frozen state, and repairs microcracks caused by freezing stress through dynamic reconstruction in a thawed state.
4. A method for preparing a self-absorbent ice bag as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: (1) preparing chitosan grafting monomer; (2) Preparation of nanosilver / zinc oxide composite antibacterial agent; (3) preparing antimicrobial agent microcapsules; (4) performing a main polymerization reaction: adding acrylic acid, sodium acrylate, a flexible crosslinking agent, a chitosan grafting monomer, biuret, a dynamic thiol compound, nano-silicon dioxide, a modified nano-silver / zinc oxide composite, a modified montmorillonite and an antibacterial agent microcapsule to deionized water in sequence, adjusting the pH to 7.0-8.0; reacting at 60-70° C. for 3 hours under nitrogen protection; drying and crushing the product to 100-200 μm; (5) Packaging.
5. The method for preparing the self-absorbent water ice bag according to claim 4, characterized in that: The steps of preparing chitosan grafted monomers include: dissolving chitosan with a deacetylation degree of ≥90% and a relative molecular weight of 100,000-200,000 in a 1% acetic acid solution, stirring until completely dissolved to form a uniform and transparent chitosan solution; performing a grafting reaction according to a mass ratio of chitosan to acrylic acid of 1:4, that is, slowly dropping the chitosan solution at a ratio of 1:4, and maintaining a stirring speed of 300 rpm; adding 0.1% initiator, reacting in a 60°C water bath for 2 hours to form a grafted modified chitosan solution; and using anhydrous ethanol for precipitation, washing, and drying at 60°C for 12 hours to obtain chitosan grafted monomer powder.
6. The method for preparing the self-absorbent water ice bag according to claim 4, characterized in that: The steps of preparing the nano silver / zinc oxide composite antibacterial agent include: dispersing 50 nm zinc oxide in deionized water with a mass concentration of 5%, ultrasonically dispersing for 30 minutes, adding 0.1% Tween-80, and continuing to stir for 1 hour to improve the dispersibility of zinc oxide; slowly dripping 0.1 mol / L silver nitrate solution into the zinc oxide dispersion to control the silver ion concentration to 2 wt%. Under stirring conditions, adding a reducing agent of 0.2 mol / L glucose solution, maintaining the reaction temperature at 80°C, reacting for 1 hour, generating surface-loaded nano silver zinc oxide composite particles; adding 1% quaternary ammonium salt solution to the nano silver / zinc oxide composite particles, stirring at 60°C for 2 hours for surface modification, then washing with deionized water for 3 times, and drying to obtain a modified nano silver / zinc oxide composite.
7. The method for preparing the self-absorbent water ice bag according to claim 4, characterized in that: The steps of preparing the antibacterial agent microcapsules include: taking antibacterial essential oil as a core material, adding a solvent to dilute it, stirring at a high speed of 1000 rpm, adding it dropwise into deionized water to form an emulsion, dissolving gelatin in deionized water at 50°C to form a 10% gelatin solution, slowly adding it into the emulsion, maintaining a stirring speed of 500 rpm, then adding a 0.5% glutaraldehyde solution with a mass ratio of 1:10 to gelatin, reacting at 50°C for 2 hours to form a stable microcapsule structure, cooling the microcapsule emulsion to room temperature after the reaction is completed, precipitating microcapsules with anhydrous ethanol, repeating washing for 3 times, and finally drying at 40°C in a vacuum drying oven for 12 hours to obtain antibacterial agent microcapsule powder.
8. The method for preparing the self-absorbent water ice bag according to claim 4, characterized in that: The main polymerization reaction step is specifically as follows: adding acrylic acid and sodium acrylate into deionized water, stirring until completely dissolved, adjusting the pH to 7.0-8.0, and under stirring conditions, sequentially adding a flexible crosslinking agent, a chitosan grafting monomer, biuret, a dynamic thiol compound, nano-silicon dioxide, a modified nano-silver / zinc oxide composite, a modified montmorillonite and an antibacterial agent microcapsule, stirring until each component is evenly dispersed, and then adding 0.1% initiator; Under nitrogen protection, the mixed solution was heated to 60-70°C, the stirring speed was maintained at 300 rpm, the reaction time was 3 hours, and after the polymerization was completed, it was cooled to room temperature to obtain a gel product; the gel was placed in an 80°C oven and dried to constant weight, and then a grinder was used to crush the dried gel into particles with a particle size of 100-200 μm to obtain the target powder product.
9. The method for preparing the self-absorbent water ice bag according to claim 4, characterized in that: The packaging step includes: using a three-layer co-extruded film, wherein the outer layer is high-density polyethylene with a thickness of 70 μm, the middle layer is ethylene-vinyl acetate copolymer with a thickness of 40 μm, and the inner layer is linear low-density polyethylene with a thickness of 50 μm, putting the prepared gel powder into the three-layer composite film bag, and sealing it with a heat sealer.
10. The method for preparing the self-absorbent water ice bag according to claim 9, characterized in that: The heat sealing process parameters of the three-layer composite film are: temperature 135±5° C.; pressure 0.6±0.1 MPa; time 1.5±0.2 s.
Citation Information
Patent Citations
Preparation method of ice bag
CN103756644A
Autonomous self-repairing elastomer with high tensile property as well as preparation method and application thereof
CN111285988A
Anti-falling ice bag and preparation method thereof
CN114574171A
Composite low-temperature phase-change cold storage agent with high cycle performance and preparation method of composite low-temperature phase-change cold storage agent
CN116004189A